2019
DOI: 10.1021/acschemneuro.9b00083
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazine-Fused Triterpenoids Block the TRPA1 Ion Channel in Vitro and Inhibit TRPA1-Mediated Acute Inflammation in Vivo

Abstract: TRPA1 is a non-selective cation channel, most famously expressed in non-myelinated nociceptors.In addition to being an important chemical and mechanical pain sensor, TRPA1 has more recently appeared to have a role in inflammation as well. Triterpenoids are natural products with antiinflammatory and anti-cancer effects in experimental models. In this paper, thirteen novel triterpenoids were created by synthetically modifying betulin, an abundant triterpenoid of the genus Betula L. and their TRPA1-modulating fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…TRPA1 is widely expressed in neuronal and non-neuronal cells, and it acts as a biological sensor that is activated by environmental irritants and oxidative-and thiol-reactive compounds [13][14][15][16][17]. Because transgenic mice lacking TRPA1 exhibit suppressed sensitivity to mechanical stimulation, cold stimuli, and TNF-α-induced mechanical hyperalgesia [18][19][20][21][22], TRPA1 has been identified as a nociceptor mediating acute and inflammatory pain [21][22][23][24][25]. On the other hand, a previous study from our group revealed the transcriptional induction of TRPA1 by inflammation via HIF-1α as a mechanism controlling inflammatory cytokine release [26].…”
Section: Introductionmentioning
confidence: 99%
“…TRPA1 is widely expressed in neuronal and non-neuronal cells, and it acts as a biological sensor that is activated by environmental irritants and oxidative-and thiol-reactive compounds [13][14][15][16][17]. Because transgenic mice lacking TRPA1 exhibit suppressed sensitivity to mechanical stimulation, cold stimuli, and TNF-α-induced mechanical hyperalgesia [18][19][20][21][22], TRPA1 has been identified as a nociceptor mediating acute and inflammatory pain [21][22][23][24][25]. On the other hand, a previous study from our group revealed the transcriptional induction of TRPA1 by inflammation via HIF-1α as a mechanism controlling inflammatory cytokine release [26].…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that TRPA1 is expressed in primary human osteoarthritic chondrocytes, and that its expression is downregulated by the antiinflammatory drugs aurothiomalate and dexamethasone [8,20]. In addition to OA, TRPA1 is also implicated in the development of other inflammatory conditions and joint diseases, such as gout and chronic arthritis [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 79%
“…Transisomer: 1 H NMR (300 MHz, CDCl 3 ): δ 7.45 (br.d, J = 8.4 Hz, 2H, o-C 6 H 4 ), 7.00 (br.d, J = 8. 4 Hz, 2H, H m-C 6 H 4 ), 6.55 (d, J = 10.5 Hz, 1H, (CH)), 3.80 and 3.78 (both s, 2 × 3H, 2 OMe), 2.42−2.12 (m, 2H, HC−CH), 1.63−1.47 and 1.44−1.31 (both m, 2 × 1H, CH 2 ). 2)), 24.9 (C(1)), 18.6 (C(3)).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Silica gel column chromatography (eluent: CHCl 3 −MeOH, 25:1) gave the desired product 12. 3,5,2,4]triazolo[1,2-a]pyridazin-5-yl)methyl)-2-(3,5-dioxo-4-phenyl-1,2,4-triazolidin-1-yl)malonate (12a). Reaction time: 2 h, yield: 60% (250 mg), yellow oil, cis/trans ≈ 3.5:1.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation